2023
DOI: 10.3390/children10071204
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Physical Fitness among Chinese Adolescents Aged 15–18: A Cross-Sectional Study of Gender Differences

Abstract: Objective: The aim of this study is to examine the relationship between varying levels of obesity and physical fitness test scores among Chinese adolescents, while also investigating gender differences in physical fitness and overall health. Data on height, weight, 50 m sprints, 1000/800 m runs, standing long jumps, sit and reach exercises, pull-ups/bent-leg sit-ups, and additional variables were collected from the DYH health database. Physical fitness indicators were evaluated based on the revised 2014 Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Scientific evidence has shown that high levels of sedentary living and physical inactivity are associated with an increased risk of obesity (Lätt et al, 2015;Liu et al, 2023;Owen et al, 2014) various cancers (Cannioto et al, 2018;Cong et al, 2014;Lee et al, 2012;Schmid & Leitzmann, 2014), cardiovascular disease (Lee et al, 2012;Sattelmair et al, 2011), diabetes (Lee et al, 2012;Liu et al, 2023;Van der Berg et al, 2016), and mortality (Löllgen et al, 2009;Wilmot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific evidence has shown that high levels of sedentary living and physical inactivity are associated with an increased risk of obesity (Lätt et al, 2015;Liu et al, 2023;Owen et al, 2014) various cancers (Cannioto et al, 2018;Cong et al, 2014;Lee et al, 2012;Schmid & Leitzmann, 2014), cardiovascular disease (Lee et al, 2012;Sattelmair et al, 2011), diabetes (Lee et al, 2012;Liu et al, 2023;Van der Berg et al, 2016), and mortality (Löllgen et al, 2009;Wilmot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%